Frenemies: understanding the interconnectedness of rival fan identities in Harare, Zimbabwe. (18th August 2018) - Chiweshe, Manase Kudzai
Abstract : Of late, the concept of 'frenemies', commonly used to explain relationships in which people are friends and enemies at the same time, has increasingly been used by social theorists to understand relationships in all forms of social life, with particular reference to friendships and relationships especially among teenagers and women in western societies. In this essay, the concept is used to understand football identities amongst fans of rival teams based in the same African city, Harare. The essay highlights how football identities fit into an intricate web of social relationships based on blood, totems, friendship, marriage and location. Football identities are often in conflict with other social identities leading to friction especially when football emerges as a topic at social gatherings. In football fan identities, formed largely in part by the presence of rival fans, are also built and sustained through celebrating difference from rivals. Using the experiences of Dynamos and Caps United football club fans in Harare on the basis of group discussions, in-depth interviews and interaction with 30 football fans, the essay explores how within the enmity of football rivalries there is scope to understand the concept of frenemies. Focusing on the love–hate relationship between the fans of city rivals, it argues that rival football fans despise each other yet still feel they belong to one football family.